Cellular structure and chemical composition of cork from the Chinese cork oak (Quercus variabilis) - Miranda, Isabel; Gominho, Jorge; Pereira, Helena (Journal of Wood Science, 2012)
Quercus variabilis Blume, the Chinese cork oak, is an oak species with a thick cork outer bark. The cork is exploited at a limited scale in China and considered of lower quality than the commercial cork from Quercus suber. We studied an industrial cork granulate feedstock of Q. variabilis in relation to cellular structure and chemical composition and compared it to Q. suber cork under a material’s perspective. The cork of Q.variabilis has 1.1 % ash, 9.6 % extractives, 34.8 % suberin and 19.1 % lignin. The monosaccharide composition with shows a predominance of hemicelluloses: glucose 42.8 % of total neutral sugars, xylose 27.5 %, arabinose 15.4 %, galactose 9.0 %, mannose 4.0 %, rhamnose 1.2 %. The FT-IR spectrum shows the indicative peaks of suberin. The composition is overall similar to that of Q. suber cork. Q. variabilis cork has the typical cellular characteristics of bark cork tissues with a regular and radially aligned structure of cells without intercellular voids. Solid volume fraction was estimated at approximately 16 %. Compared with Q. suber, the Q. variabilis cork cells are smaller, the cell wall undulation and the overall row alignment less homogeneous, the cell surface is irregular and the solid volume proportion higher. The characteristics of Q. variabilis cork support its use as a cellular material for sealing, insulation and energy absorption, but the overall quality is lower than that of Q. suber cork. The negative impact of the higher density and structural lower uniformity at tissue and cell level should be evaluated for processing and product performance.
Keywords: Cellular structure; Cork; Quercus suber; Quercus variabilis; suberin